2017
DOI: 10.1111/jan.13308
|View full text |Cite
|
Sign up to set email alerts
|

Which interval is most crucial to presentation and survival in gastroesophageal cancer: A systematic review

Abstract: Further research into the patient interval is required to elicit information on how and why patients present with their cancer symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The study confirms the median age of 64.4 for symptom onset for oesophageal cancer with no oesophageal cancer cases seen below 43 years. This is consistent with the majority of other epidemiological studies 14–17 . In contrast, gastric cancer peaked in the older 70–79 age group, with a median age of 69.6 years, and appears more unpredictable in age onset, with one case occurring in the third decade.…”
Section: Discussionsupporting
confidence: 91%
“…The study confirms the median age of 64.4 for symptom onset for oesophageal cancer with no oesophageal cancer cases seen below 43 years. This is consistent with the majority of other epidemiological studies 14–17 . In contrast, gastric cancer peaked in the older 70–79 age group, with a median age of 69.6 years, and appears more unpredictable in age onset, with one case occurring in the third decade.…”
Section: Discussionsupporting
confidence: 91%
“…According to the literature, shortening the patient interval is probably most vital to reduce delay in the diagnostic pathway of gastroesophageal cancer. 7,8 In gatekeeper systems like that in the Netherlands, patients have to visit a general practitioner (GP) first and GPs can refer patients to secondary care if needed. Most patients with UGI cancer will therefore initially present with symptoms in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, however, patients with oesophageal cancer frequently arrived late in presentation and commonly referred late to the appropriate health facilities. In addition, literature also showed that shortening the time to presentation is an important step in reducing late diagnosis, and improving the prognosis and survival of patients with oesophageal cancer 12 13…”
Section: Introductionmentioning
confidence: 99%
“…In addition, literature also showed that shortening the time to presentation is an important step in reducing late diagnosis, and improving the prognosis and survival of patients with oesophageal cancer. 12 13 …”
Section: Introductionmentioning
confidence: 99%